The Effectiveness of Anti-Anemia Teenage Cadre Training On Adolescent Knowledge - Herawati Herawati; Triana Indrayani; Bunga Tiara Carolin (STRADA : Jurnal Ilmiah Kesehatan, 2020)
The method used in this study was the Quasy-experimental method. The research design used in this study was one group (of) pretest posttest design. The number of samples in this study, ranged in age from 16 to 19 y.o from 4 schools in Jayanti PHC, was as many as 40 people. The sampling technique used was purposive sampling technique.The research instrument consisted of a questionnaire about adolescent knowledge in adolescent anemia. Data were analyzed using paired t-test. The results show that there were differences in knowledge scores before and after the training was given. The obtained research significance value (2-tailed) was 0,000 <0.05. There is an influence of anti-anemia teenage cadre training on adolescent knowledge.